Menumbuhkan Daya Tarik Program Studi Bioteknologi Melalui Sinergi Marketing Mix (4p) dan Service Excellence Orientation di Institut Teknologi Del - Saragih, Diego; Sihombing, Adiguna; Manalu, Septiana; Sitinjak, Gracia (Riviera Publishing, 2025)
The Biotechnology Study Program at the Del Institute of Technology is a new study program that was opened in 2025, requiring an appropriate strategy to increase its attractiveness amidst the competition in higher education. This study aims to analyze the influence of the Marketing Mix (4P) consisting of product, price, place, and promotion, as well as Service Excellence Orientation, on the attractiveness of the Biotechnology Study Program at the Del Institute of Technology. The research approach uses the Service-Dominant Logic (SDL) framework that emphasizes value creation through interactions between the institution and prospective students. The attractiveness of the study program is understood as prospective students' perceptions of relevance, value, career prospects, and initial experience of the services received. This study highlights that the educational product includes not only the curriculum but also the program's reputation, laboratory facilities, and academic services. Price perception is influenced by affordability, fairness, and the suitability of costs to the benefits obtained. Place encompasses physical and digital accessibility and the completeness of learning facilities, while promotion plays a role in communicating the excellence of the study program through various media and marketing activities. Furthermore, Service Excellence Orientation is a crucial factor in building a positive and sustainable service experience. The study results indicate that the synergy between the Marketing Mix (4P) and Service Excellence Orientation has the potential to significantly increase the attractiveness of the Biotechnology Study Program, thus serving as a strategic basis for the development and marketing of new study programs at the Del Institute of Technology.